Principles of Good Faith in the Reimbursement of Expenses within Oil and Gas Revenue Sharing Agreements in Indonesia - Nurarafah, Nurarafah; Kamello, Tan; Yahya, Azhari; Dahlan, Dahlan; Jarnawi, Jarnawi (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This study seeks to examine and elucidate the significance of the principle of good faith within the national legal framework, as well as to develop norms pertaining to good faith in the context of operational cost recovery for production sharing contracts in Indonesia's oil and gas industry. This study utilizes a normative legal methodology alongside a legislative framework. The sources of data encompass essential legal materials, including legislation, journal articles, books, and pertinent research reports that contribute to the discourse. The analysis of the data is performed qualitatively through a juridical-philosophical lens, developing arguments rooted in legal philosophy, legal theory, and various legal principles. The findings reveal that the principle of good faith in the operational cost recovery of production sharing contracts in Indonesia is governed at each stage of the contract to safeguard the interests of disadvantaged parties. This regulation addresses the essential principle of good faith that all parties must adhere to in order to guarantee the equitable execution of rights and obligations. In the context of operational cost recovery for production sharing contracts in Indonesia, good faith is characterized by adherence to and compliance with audit results, reflecting a commitment to the proper execution of the business contract's terms. The operational cost recovery system is anticipated to serve as a reimbursement mechanism for expenses associated with oil and gas production.